FORMULATION, EVALUATION, AND ANTIBACTERIAL TESTING OF JATROPHA CURCAS L. GUM TOOTHPASTE PREPARATIONS. (Journal of Health, Technology and Science (JHTS), 2025)
Dental caries remains a significant problem in Indonesia due to the activity of Streptococcus mutans, which damages tooth enamel. Prevention is done by brushing your teeth and using antibacterial toothpaste. Jatropha curcas L. sap has the potential to be a natural antibacterial agent because it contains flavonoids, tannins, saponins, and alkaloids. This study aims to determine the optimal formulation, evaluate toothpaste containing fence post gum as an antibacterial active ingredient, and assess its effectiveness against S. mutans. The research was conducted experimentally in a laboratory using a quantitative approach. Rubber samples were taken from Motinelo Village, Tabongo District, Gorontalo Regency. The toothpaste was formulated at 4%, 8%, and 16% castor oil extract (F1, F2, and F3) and tested for physical characteristics and antibacterial activity using the disk diffusion method. The results show that all formulas meet the physical quality standards outlined in SNI 12-3524-1995. Formula F3 (16%) had the largest inhibition zone and the most potent antibacterial activity, while F2 and F3 were not significantly different and were more effective than the positive control. Antibacterial activity is influenced by the flavonoid, saponin, tannin, and alkaloid content, which damage cell walls and inhibit bacterial metabolism. It is concluded that toothpaste containing fence post gum is effective at inhibiting Streptococcus mutans and has the potential to serve as a natural ingredient for maintaining dental and oral health.
Keywords: Jatropha curcas L., herbal toothpaste, Streptococcus mutans, antibacterial, formulation